La normalisation comptable internationale par l’IASB - Danjou, Philippe (INSEE, 2017)
Cette note, préparée pour le 16ème colloque de l’ACN, a pour objet d’exposer de façon succincte les origines du mécanisme d’harmonisation internationale des normes comptables IFRS dans le secteur privé, les modalités de fonctionnement de l’organisme qui édicte ces normes, la façon elles sont transposées dans la règlementation. On y présentera l’état des lieux en matière d’adoption internationale. Enfin, le processus d’élaboration d’une norme IFRS sera illustré par un survol des travaux ayant abouti à la publication récente de la norme IFRS 16 « Contrats de location ».

The Application of CISG in International Arbitration - Cisár, Ivan (Current Issues of International Commercial Arbitration, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION